Possible role of locus coeruleus neuronal loss in age-related memory and attention deficits - Gargano, Alessandra; Olabiyi, Bolanle Fatimat; Palmisano, Michela; Zimmer, Andreas; Bilkei-Gorzo, Andras (Frontiers in Neuroscience, 2023)
Aging is associated with a decline in cognitive abilities, including memory and attention. It is generally accepted that age-related histological changes such as increased neuroinflammatory glial activity and a reduction in the number of specific neuronal populations contribute to cognitive aging. Noradrenergic neurons in the locus coeruleus (LC) undergo an approximately 20 % loss during ageing both in humans and mice, but whether this change contributes to cognitive deficits is not known. To address this issue, we asked whether a similar loss of LC neurons in young animals as observed in aged animals impairs memory and attention, cognitive domains that are both influenced by the noradrenergic system and impaired in aging. For that, we treated young healthy mice with DSP-4, a toxin that specifically kills LC nordrenergic neurons. We compared the performance of DSP-4 treated young mice with the performance of aged mice in models of attention and memory. To do this, we first determined the dose of DSP-4, which causes a similar 20 % neuronal loss as is typical in aged animals. Young mice treated with DSP-4 showed impaired attention in the presence of distractor and memory deficits in the 5-choice serial reaction time test (5-CSRTT). Old, untreated mice showed severe deficits in both the 5-CSRTT and in fear extinction tests. Our data now suggest that a reduction in the number of LC neurons contributes to impaired working memory and greater distractibility in attentional tasks but not to deficits in fear extinction. We hypothesize that the moderate loss of LC noradrenergic neurons during aging contributes to attention deficits and working memory impairments.